2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4650500
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of monitoring congestive heart failure by multiple impedance vectors

Abstract: All impedance vectors decreased during CHF. Impedance measurement employing left heart sensors correlated well wit- - h LA pressure, and may improve detection of CHF onset compared to sensing by RA or RV leads alone. This approach has important clinical implications for managing heart failure patients in the ambulatory setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
3
8
0
Order By: Relevance
“…To our knowledge, the present study is the first to investigate ICZ variations in humans by using a permanent biventricular pacing system. Previous studies evaluating multiple ICZ vectors have been performed in animal experimental models, therefore in different structural anatomical contexts 13,18,19 . Our results not only suggest that ICZ measurement by biventricular lead electrodes is feasible and can be applied to the human heart, but also seem to be in line with the available animal data, with regard to the correlation between ICZ and hemodynamic variables 13,18,19 …”
Section: Discussionsupporting
confidence: 79%
“…To our knowledge, the present study is the first to investigate ICZ variations in humans by using a permanent biventricular pacing system. Previous studies evaluating multiple ICZ vectors have been performed in animal experimental models, therefore in different structural anatomical contexts 13,18,19 . Our results not only suggest that ICZ measurement by biventricular lead electrodes is feasible and can be applied to the human heart, but also seem to be in line with the available animal data, with regard to the correlation between ICZ and hemodynamic variables 13,18,19 …”
Section: Discussionsupporting
confidence: 79%
“…Stahl et al 17 showed a strong correlation between intracardiac impedance parameters and stroke volume in a porcine model. Panescu et al 18 examined multiple impedance vectors derived from implanted biventricular implantable cardioverter-defibrillator devices in a canine/ovine model of heart failure, and demonstrated good correlation between cardiogenic impedance and progression of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…With currents flowing between intracardiac electrodes (RV, LV, and RA) and to the CIED casing, enlargement in ventricular volumes will decrease the impedance since more of the heart is encompassed by these impedance vectors. Four intrathoracic and 2 intracardiac vectors were examined in 16 dogs and 5 sheep [63]. Impedance values measured by all vectors decreased with the onset of HF, with the maximum decrease occurring with LV‐Can and LV–RV.…”
Section: Sensors For Heart Failure (Table 2)mentioning
confidence: 99%